1990
DOI: 10.1097/00000658-199010000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Growth Hormone on Donor-site Healing in Severely Burned Children

Abstract: The beneficial effects of growth hormone on wound healing in severely burned children were studied. Forty patients who were 2 to 18 years old, with 40% or more total body surface area (TBSA) and 20% or more TBSA full-thickness flame or scald burns, were randomized in a double-blind study to receive placebo or 0.1 mg/kg/day recombinant human growth hormone (rHGH) until the first donor site healed or to receive 0.2 mg/kg/day rHGH or placebo from admission throughout hospitalization. Patients receiving 0.2 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
133
1
9

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(143 citation statements)
references
References 15 publications
0
133
1
9
Order By: Relevance
“…14,21 There is evidence that rhGH improves wound healing through stimulation of IGF-I. 9,17,22,23 In turn, IGF-I enhances wound healing by stimulating collagen formation and mitogenicity in fibroblasts and keratinocytes by binding to their receptors. 17,23 In this study we show that the administration of liposome-encapsulated IGF-I cDNA constructs improved the area of burn wound reepithelization as well as wound linear re-epithelization when compared with rhIGF-I protein or liposomes containing the lacZ gene for ␤-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
“…14,21 There is evidence that rhGH improves wound healing through stimulation of IGF-I. 9,17,22,23 In turn, IGF-I enhances wound healing by stimulating collagen formation and mitogenicity in fibroblasts and keratinocytes by binding to their receptors. 17,23 In this study we show that the administration of liposome-encapsulated IGF-I cDNA constructs improved the area of burn wound reepithelization as well as wound linear re-epithelization when compared with rhIGF-I protein or liposomes containing the lacZ gene for ␤-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of transfection, transcription, and translation in the skin and systemic cells were based on ␤-galactosidase and IGF-I expression. The biological efficacy of the translated IGF-I gene was evaluated by the mitogenic activity in dermal cells and the rate of re-epithelization (Herndon et al, 1990;Martin, 1997).…”
mentioning
confidence: 99%
“…Ramirez et al 23 , reported that it was observed in 30 patients from 48 in rhGH group and 22 from 54 in placebo group. Herndon et al reported hyperglycemia in 2 of 10 patients of rhGH group versus none in placebo group 21 . Hart et al 24 reported that it was not observed in none of 19 patients in treatment group and 21 from placebo group.…”
Section: Resultsmentioning
confidence: 98%
“…All trials used the subcutaneous or intramuscular rhGH administration route and the therapy was given at least for 7 days. Effects of rhGH on donor site healing: Gilpin 20 and Herndon 21 involved a total of 48 burned children in treatment group with rhGH, versus 44 placebo-controls. The treatment was effective in reducing donor-site time healing (Weighted Mean Difference: -1.77 day, p < 0.00001 for overall effect).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation